Epistemology and practice : Durkheim's The elementary forms of religious life - Rawls, Anne Warfield, 1950- (Cambridge University Press, 2004)
In this original and controversial book Professor Rawls argues that Durkheim's The Elementary Forms of Religious Life has been consistently misunderstood. It is his crowning achievement and an attempt to establish a unique epistemological basis for the study of sociology and moral relations.